2020
DOI: 10.1002/ppul.24720
|View full text |Cite
|
Sign up to set email alerts
|

Lung ultrasound evaluation of incremental PEEP recruitment maneuver in children undergoing cardiac surgery

Abstract: Aim To explore the effect of incremental positive end‐expiratory pressure recruitment maneuver (iPEEPRM) in children with congenital heart diseases (CHDs) using lung ultrasound. Methods Thirty‐six children aged 3 months to 5 years scheduled for cardiac surgery participated. iPEEPRM was performed with PEEP stepwise increase (0‐5‐10‐15 cmH2O) and decrease at the same rate before and after surgery. Atelectatic areas, ultrasound scores, arterial oxygen pressure (PaO2), and respiratory system dynamic compliance per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…It is crucial to closely monitor the patient immediately after completion of the cardiac surgery for the unexpected hemodynamic swings 15,21 . Our previous study 15 revealed that a higher incidence of hemodynamic repercussions was found when 10 breaths (20–30 s) were maintained at each step. In the study by Song et al, 7 there were no severe hemodynamic events recorded if PEEP was held at each level only for 5 s during RM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is crucial to closely monitor the patient immediately after completion of the cardiac surgery for the unexpected hemodynamic swings 15,21 . Our previous study 15 revealed that a higher incidence of hemodynamic repercussions was found when 10 breaths (20–30 s) were maintained at each step. In the study by Song et al, 7 there were no severe hemodynamic events recorded if PEEP was held at each level only for 5 s during RM.…”
Section: Discussionmentioning
confidence: 99%
“…Hemodynamic events were recorded and defined as ≥20% changes from baseline. The atelectatic areas were measured using ImageJ version 1.31 (Mac OS X; National Institutes of Health) 14,15 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of POCUS to guide recruitment maneuvers in pediatric surgery patients with atelectatic lung has also been reported recently. 7,8 We also perform a bilateral lung ultrasound examination prior to extubation and discharge from the recovery room. This confirms lung sliding or B-lines (rule-out pneumothorax) and identifies residual atelectasis or effusion that may need intervention.…”
Section: Discussionmentioning
confidence: 99%
“…A well-trained blinded anesthesiologist will perform all lung ultrasound scans using SonoSite M-Turbo with a 5-12 MHz linear transducer. Patients will be scanned in the supine position following the lung ultrasound method described by Sun et al [39]. Brie y, six regions will be scanned in each hemithorax.…”
Section: Pulmonary Ultrasonographymentioning
confidence: 99%